Features of current and intensive therapy of new coronavirus infection in children with comorbidities (clinical cases) - K. V. Pshenisnov; Yu. S. Aleksandrovich; V. A. Kaziakhmedov; M. M. Kostik; I. A. Kondrashev (Журнал инфектологии, 2020)
The risk of a severe course of new coronavirus infection (COVID-19) due to the development of acute respiratory distress syndrome is extremely high, which is especially true for patients with comorbidities. The aim of the study is to demonstrate the peculiarities of the course and intensive care measures in new coronavirus infection COVID-19 in children with comorbidities. Patients and methods: On the example of clinical cases, the characteristics of the course of a new coronavirus infection of COVID-19 in children with systemic lupus erythematosus and bronchopulmonary dysplasia are considered. Results: The main data from the history and clinical laboratory examination are reflected, which made it possible to identify a cytokine storm in a timely manner, a high risk of adverse course and begin timely specific pathogenetic therapy, including immunoglobulins for intravenous administration, hydroxychloroquine, ritonavir in combination with lopinavir, azithromycin and dexamethasone. Particular attention is paid to the need to limit infusion therapy, maintain a negative water balance and optimal blood oxygen capacity, ambiguity of opinions on the need for routine use of albumin and dexamethasone solutions in patients with COVID-19 has been demonstrated. Conclusion: Children with comorbidities are characterized by a severe course of a new coronavirus infection COVID-19, which requires timely pathogenetic therapy taking into account the individual characteristics of the patient.